PENGGUNAAN METODE MULAZAMAH DALAM MENDISIPLINKAN SHALAT PESERTA DIDIK DI Madrasah Tsanawiyah Negeri 3 SIJUNJUNG - Ansyarina, Hafizni (JURNAL ISLAMIKA, 2022)
Salat is a mandatory prayer for every Muslim who has puberty and be intelligent. The position of prayer occupies an important position in Islam so it is said that who performs the prayer means to have established agam and who leaves the prayer means to have broken down the religion. Students of MTs Negeri 3 Sijunjung in general have been obliged to perform fardhu prayers, but in reality there are still many who are lazy and undisciplined to fulfill it. This research reveals the cause of the undisciplined students of MTs Negeri 3 sijunjung in performing prayers and explaining the efforts of teachers and dormitory builders in overcoming it by using the mulazamah method. The results showed that the cause of students of MTs Negeri 3 Sijunjung lack discipline in performing prayers was due to lazy factors and late wake up in the morning. While the efforts of teachers and dormitory builders in overcoming the problem of indiscipline of learners in performing prayers is to apply the mulazamah method with its activities: providing understanding and transparency to learners, providing women's study, giving reaword, giving reaword or punishment, consistent, flexible, being assertive, patient and unemotional. The mulazamah method with its various activities has succeeded in disciplining the prayers of learners in sijunjung State MTs.